PENILAIAN KINERJA KOPERASI WANITA SERBA USAHA “SETIA BUDI WANITA” JAWA TIMUR BERDASARKAN PERATURAN MENTERI NO.14/PER/M.KUKM/XII/2009 (PERIODE PENELITIAN 2010-2012) - Faqih Fansuri; Achmad Helmy Djawahir (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Performance is an illustration of the level achievement of an activity/program/​policy implementation in achieving goals, objectives, mission and vision of the organization as stated in the strategic planning. Financial performance assessment was conducted to determine how far the performance of cooperative can support its achievement. It is expected to give consideration and information material to help management make a decision that can improve its goal achievement. The purpose of this study was to determine the performance and the health level of Women Multipurpose Cooperative Enterprises